2018
DOI: 10.1044/2017_ajslp-16-0196
|View full text |Cite
|
Sign up to set email alerts
|

What Matters in Semantic Feature Analysis: Practice-Related Predictors of Treatment Response in Aphasia

Abstract: https://doi.org/10.23641/asha.5734113.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…However, Gravier et al (2018) found that response to treatment was more accurately predicted by the number of features generated by a participant during SFA than either total treatment time or the average number of treatment trials in their treatment study also using SFA for anomia with 17 participants.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, Gravier et al (2018) found that response to treatment was more accurately predicted by the number of features generated by a participant during SFA than either total treatment time or the average number of treatment trials in their treatment study also using SFA for anomia with 17 participants.…”
Section: Discussionmentioning
confidence: 94%
“…Wambaugh Mauszycki & Wright, 2014;Wambaugh & Ferguson, 2007). In SFA treatment, the likely active ingredient of treatment is the generation of semantic features for a target word (see Gravier et al, 2018). Thus SFA for nouns includes generating the semantic feature of category whereas in SFA adapted for verbs, features unique to verbs (and therefore potentially active ingredients of treatment for them) are generated (e.g.…”
Section: Verb Retrieval Deficits In Aphasia: Theory and Therapymentioning
confidence: 99%
“…Notably, published SFA protocols have incorporated procedures consistent with the principles of experience-dependent neuroplasticity (Kleim and Jones 2008) and other motor learning principles (Maas et al 2008), which are thought to improve treatment, maintenance and generalization effects. More specifically, these principles have included high practice intensity within session, high frequency of sessions, high salience (e.g., self-generating personalized semantic feature descriptions; Boyle 2004), randomized order of stimulus presentation, varied practice (i.e., multiple pictures to represent each stimulus word), and intermittent feedback on accuracy (e.g., Efstratiadou et al 2018, Gravier et al 2018, Quique et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Such effortful conditions are often described as errorful therapy, as individuals are made aware of their errors, and have been found to be particularly beneficial in naming rehabilitation as they call the individual to draw information from long-term memory (3, 21,22). Furthermore, there is evidence that the practice of autonomously retrieving a stimulus name, even when incorrect, improves treatment outcomes (2,(22)(23)(24)(25). Moreover, greater long-term retention is observed particularly in conditions of effort, consistent with the principle that repeated retrieval practice improves access to stored information (2,3,22).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Villard and Kiran (35) suggest that attention, or the lack thereof, can greatly influence not only the naming performance but also the language treatment outcomes. Furthermore, the importance of the quality, in addition to the quantity of practice, cannot be overlooked in evaluating treatment (46,47). While a frequent and well-spaced dosage of treatment is necessary for improvement (3,12), the quality of treatment, as shaped by speech therapist input and client output (24), must be considered.…”
Section: Introductionmentioning
confidence: 99%